A multi-medium chain modeling approach to estimate the cumulative effects of cadmium pollution on human health. (August 2018) - Liu, Xingmei; Zhong, Libin; Meng, Jun; Wang, Fan; Zhang, Jiangjiang; Zhi, Yuyou; Zeng, Lingzao; Tang, Xianjin; Xu, Jianming
Abstract: Cadmium is a highly persistent and toxic heavy metal that poses severe health risks to humans. Diet is the primary source of human exposure to cadmium, especially in China. Soil, as the main medium that transfers cadmium to rice, can be used as a helpful indicator to predict human exposure to cadmium in soils. There is, however, very little work that links a soil-rice transfer model with a biokinetic model to assess health risks. In this work, we introduce a multi-medium chain model based upon a soil-rice-human continuum to address this issue. The model consists of three basic steps: (i) development and validation of a soil-rice transfer model for cadmium based on 189 pairs of measured data in Wenling of Zhejiang province in Southeast China; (ii) calculation of weekly exposure based on the nationwide monitoring and survey results; (iii) linking the exposure model with a modified biokinetic model proposed with a classic biokinetic model to predict urinary cadmium, which is a biomarker to assess the health risks. Results indicated that the developed soil-rice-human transfer model predicted well the urinary cadmium levels in humans subjected to age and exposure uncertainties. We observed a maximum of 0.71 μg g −1 creatinine in males and 1.53 μg g −1 creatinine in females at 70 years old under median cadmium exposure, which was consistent with previous studies. Sensitive analysis was also conducted to detect the sensitive parameters that have the most significant influences on the output of the model. The new risk assessment strategy proposed in this work is beneficial for predicting the cumulative cadmium levels in various exposed populations so that we can quickly identify the critical areas from basic soil properties. Graphical abstract: Image 1 Highlights: This is the first soil-rice-human chain model to evaluate cumulative cadmium risks in humans. Cadmium transfer from soil to rice is validated using measured data from the rice paddies. Urinary cadmium excretion is predicted subject to age and exposure uncertainties. Global sensitive analysis (GSA) is applied to determine influential parameters. Abstract : First chain model through soil-plant-human continuum to calculate the potential cumulative cadmium levels in various exposed populations.